A56 ENDOSCOPIC PROCEDURE REPORT COMPLETENESS IMPROVES FOLLOWING IMPLEMENTATION OF A DICTATION TEMPLATE AT ST. PAUL'S HOSPITAL. (1st March 2018) - Yonge, J; Harris, N; Galorport, C; Suzuki, M; Amar, J; Bressler, B; Brown, C; Lam, E; Phang, T; Ramji, A; Whittaker, S; Telford, J J; et al.
Abstract: Background: Following colonoscopy or esophagogastroduodenoscopy (EGD), the physician reports their findings, which are typically transcribed and kept in patient's medical records. The completeness of endoscopic dictation reports are quality indicators for endoscopic practice. Several guidelines outlining the key elements of endoscopic reports were used to develop a dictation template at St. Paul's Hospital in 2013. Aims: The purpose of this study is to assess and compare the quality and completeness of endoscopic procedure reports from 2008 and 2014 for physicians currently working at St. Paul's Hospital to determine if key quality elements of documentation were more consistently included following institution of a dictation template. Methods: A retrospective chart review of endoscopic reports of 9 physicians were reviewed at two time points, before (2008) and after (2014) the introduction of the dictation template. 150 charts were reviewed for each doctor in each year. Data was collected from a comprehensive EMR review that included demographics, patient history, procedure report details (appropriate quality indicators as outlined by ASGE Guidelines), and length of procedure. Cecal visualization rate and polyp detection rate were also calculated for colonoscopy reports. This study was approved by the IRB at St Paul's Hospital. Results: The overall completeness for colonoscopy reporting for all quality data points improved from 70.5% in 2008 to 90.6% in 2014 (p<0.001) when looking at all variables that were included on the dictation template. The overall completeness for EGD data points improved from 81.1% in 2008 to 87.1% in 2014 (p<0.001). Most variables remained consistent or increased; however, reporting of comorbidities, medications, and patient comfort remained low at both time periods for both endoscopic procedures. The biggest improvement in reporting was seen in withdrawal time for colonoscopy and consent for EGD. Conclusions: The use of the dictation template has improved documentation of quality parameters from 2008 to 2014 in both colonoscopy and EGD. Most variables not included in the dictation template were frequently underreported and educational maneuvers as well as other adjustments to include these variables in future procedure reports can be targeted at these items. Funding Agencies: None